2014
DOI: 10.1016/j.mspro.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation and Crystallization Study of Rare Earth Metaborate Glasses

Abstract: International audienceBesides their interesting optical properties, Rare Earths (RE) can be found abundantly as fission products at the end of the nuclearfuel cycle. After reprocessing, they are stored by dissolution in a borosilicate glassy matrix. RE are also used to simulateactinides when studying nuclear waste immobilization. It is very important to understand the environment of RE in such complexglasses. Moreover, composition changes can strongly affect RE solubility in the glass melt and RE-rich phases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Previous studies on a RE-rich 7-oxides borosilicate glass, used as a model for nuclear waste glass developed to immobilize high concentration of waste, showed that the incorporation of RE 3+ ions was greatly impacted by variations of B2O3 content, which could be due to the existence of a structural relationship between RE and B in the glassy structure [3], while studies performed on other RE-rich borosilicate glasses suggest the formation of a local RE-metaborate structure incorporating preferentially RE 3+ ions [4,5,6]. To improve the understanding of RErich borosilicate glasses structure and also to enhance the immobilization properties of nuclear waste glasses, it is thus of great interest to elucidate the chemical and structural relationship that could exist between boron and RE in glasses, starting with the simplest systems bearing simultaneously these two oxides, like B2O3-RE2O3 binary system [7,8,9,10] or SiO2-B2O3-RE2O3 ternary system, and then progressively increasing the complexity of the glass composition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on a RE-rich 7-oxides borosilicate glass, used as a model for nuclear waste glass developed to immobilize high concentration of waste, showed that the incorporation of RE 3+ ions was greatly impacted by variations of B2O3 content, which could be due to the existence of a structural relationship between RE and B in the glassy structure [3], while studies performed on other RE-rich borosilicate glasses suggest the formation of a local RE-metaborate structure incorporating preferentially RE 3+ ions [4,5,6]. To improve the understanding of RErich borosilicate glasses structure and also to enhance the immobilization properties of nuclear waste glasses, it is thus of great interest to elucidate the chemical and structural relationship that could exist between boron and RE in glasses, starting with the simplest systems bearing simultaneously these two oxides, like B2O3-RE2O3 binary system [7,8,9,10] or SiO2-B2O3-RE2O3 ternary system, and then progressively increasing the complexity of the glass composition.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed to be between 3.2 and 4.5 according to [17]. [20] for the Nd 3+ absorption spectrum of crystalline Nd-metaborate). Significant differences are also observed between the spectroscopic data of this glass and of the Na-borate and Na-silicate glasses of this study that are detailed in the following.…”
Section: Discussionmentioning
confidence: 99%
“…6). However, the comparison of the data of the glassy and crystalline forms allows making an important distinction: (i) the Nd 3+ 4 I 9/2 → 2 P 1/2 absorption band is located at 428.5 nm in the crystal versus 429.8 nm in the glass [20] indicating a higher covalency in the glass (nephelauxetic effect). This is also confirmed by the 5 D 0 → 7 F 4 transition, considerably more intense in the crystal than in the glass [23], suggesting that the electronic density on the oxygens is higher in the glass, (ii) the mean Nd-O distance in the glass is significantly lower than in the crystal (respectively 2.48 Å and 2.56 Å) and (iii) the R ratio in the glass is much higher than in the crystal (respectively 2.4 and 0.4).…”
Section: Non-gaussian Broadening Of the 7 F 1 Stark Components And Enmentioning
confidence: 99%
See 2 more Smart Citations